Alguns aspectos sobre o calórico e o diâmetro dos átomos no trabalho de John Dalton - Lobato, César de Barros (2011)
From a detailed analysis of documents, we realize that historiography does not give due importance to the concepts of caloric and atomic diameter inside the atomic theory developed by John Dalton (1766-1844). In this sense, this thesis aims mainly to show the relevance of these ideas within the Daltonian atomism. We believe they are as important as the atomic weight and need to be better discussed by historiography. Thus, seeking to validate this hypothesis, this work intends to demonstrate two things. The first is to highlight the features that make so special the atomics weights inside the atomic theory, from the point of view Dalton as the point of view of historians. The second is to show that the concept of atomic diameter amalgamated with caloric also have such characteristics and therefore are as important as the idea of atomic weight to Dalton. Through the study, we could see that from the point of view of Dalton, the ideas of atomic weight and diameter are complementary, because one explains the gravimetric results, the other, the results volumetric of the reactions